A new species of Gomesa (Oncidiinae, Orchidaceae) from inselbergs in Brazilian caatinga: morphological and karyological evidence - Cordeiro, Joel M. P.; Nollet, Felipe; Buril, Maria Teresa; Chase, Mark W.; Felix, Leonardo P. (Phytotaxa, 2018)
We describe a new species of Gomesa (Oncidiinae, Orchidaceae), Gomesa caatingana, with restricted distribution on caatinga inselbergs in Paraíba and Pernambuco States, Brazil. Morphological and karyological characters of the new species were compared with those of Gomesa flexuosa, which is morphologically the most closely related species. Differences in geographical distribution, habit, flower morphology and chromosome number support description of this new species.